Single-chamber versus dual-chamber pacing in very elderly patients with sinus node disease and AV block: a real-world study. (3rd October 2022) - Bedir, A; Nageye, F; Cherek, P; Godley, C; Ghani, S; Cheong, J; D'Souza, S; Cecaro, F; Petzer, E; Martin, W; Kabunga, P
Abstract: Background: Elderly patients with sinus-node disease, have been reported to have better clinical outcomes with dual-chamber pacing compared with single chamber pacing. In contrast, randomized studies have shown no clinical benefit of dual-chamber pacing compared to single-chamber pacing in the elderly with high grade AV block., For truly elderly patients (>80 years), the optimal choice of pacing mode remains uncertain. In this real-world observational study, we analysed the clinical outcomes in a cohort of very elderly patients. Methods: We analysed retrospective data of all new pacemaker implantations for sinus node disease or high-grade atrioventricular block in patients ≥80 years a district general hospital in south-east England, UK over a 7-year period. Patients with an existing diagnosis of stroke, congestive cardiac failure and/or atrial fibrillation (AF) were excluded from the study. Patients were categorised into two analysis cohorts based on pacing mode, i.e dual chamber (DDD) pacing versus single chamber (VVI) pacing. Clinical outcome data including all-cause mortality, new onset AF and CCF were recorded. Results: A total of 208 patients were included in the study, of which 117 received (DDD) pacing vs 91 who underwent VVI pacing. The mean age was 85.8 years (84.63 DDD, 87.3 VVI, p=0.01). Single chamber pacing was associated with greater all-cause mortality (51.7% vs 31.5%, p=0.01). 23.1% of patients who underwent DDD pacing developed AF, vs 21.9% who underwent VVI pacing (p=0.85). Congestive cardiac failure was observed in 6.48% of patients who received DDD pacing vs 8.14% of patients who received VVI pacing, (p=0.66). Conclusions: In this real-world observational study of very elderly patients with sinus node disease and/or high-grade AV block, single chamber pacing was associated with a greater all-cause mortality. However, the pacing mode did not affect the incidence of atrial fibrillation and congestive cardiac failure. Funding Acknowledgement: Type of funding sources: None.